Value co-creation in B2B service business : Discovering data-driven marketing opportunities in global after-sales operations - Edelman, Pasi (My University, 2020)
All companies need data. Collected and analyzed data is already a key driver in many common business practices, and its increasing potential in B2C marketing purposes is noticed during the recent years. At the same time, as B2B business operations are generating more data than ever before, the potential of utilize customer data in B2B practices, especially in marketing and value co-creation, is still not fully released. This master’s thesis is made as a commission for the case company, Maillefer Extrusion Oy. The purpose of this thesis is to introduce practical, data-driven, constructions to support the case company’s after-sales department future growth. The theoretical background of this study includes comprehensive study of theoretical service discussion, focusing mainly on value creation and value co-creation mechanisms. Another side of the theoretical framework is to introduce customer data and its possibilities in B2B value co-creation context. This study is constructive by nature and the qualitative research data is collected mainly from eight theme interviews, where both the case company’s personnel and customers were represented. The aim in empirical research was to reveal current marketing practices and challenges in after-sales operations. Also, research the possibilities for increased customer data utilization in marketing practices and in value co-creation. The empirical research data was mainly collected in Finnish and later translated to English. In general, the empirical research confirms the notions in theoretical discussion regarding value co-creation, the successful value co-creation in B2B context requires commitment from both sides. The empirical research also highlighted the importance of coherent information and symmetric internal communication. In order to support the after-sales growth, utilize the collected customer data efficiently and co-create value in after-sales marketing, the internal communication must be respectively symmetric, existing customer data must be correct and well structured. This study provides also a systematic approach for developing the current after-sales practices towards advanced, data-based solutions for value co-creation. This study provides a coherent base for longitudinal research in future. The research in future may focus on implementing the introduced constructions and developing them further. Also, the future research may focus on application development that aim to co-create value in real-time based on collected customer data.

Kaikki yritykset tarvitsevat dataa omissa toiminnoissaan. Kerätty data ja sen analysointi on jo nykyään avainasemassa monissa liiketoiminnan eri käytännöissä. Näiden lisäksi datan hyötykäytön potentiaali on viime vuosien aikana havaittu ja sitä hyödynnetään erityisesti B2C markkinoinnin eri sovelluksissa. Samalla kun B2B liiketoiminnan eri osa-alueet tuottavat valtavasti dataa, kerätyn datan hyötykäyttö on toisaalta vielä varsin vähäistä ja sen potentiaali on valtaosin hyödyntämättä, erityisesti markkinoinnissa ja arvon yhteisluonnissa. Tämä Pro Gradu -tutkielma on tehty toimeksiantona Maillefer Extrusion Oy:lle. Tutkielman tarkoituksena on esitellä käytännöllisiä, dataan pohjautuvia konstruktioita, joita hyödyntämällä voidaan kehittää arvon yhteisluontia ja tukea asiakasyrityksen jälkimarkkinoiden sekä palveluliiketoiminnan myynnin kasvua. Tutkimuksen teoreettisessa viitekehyksessä tarkastellaan modernia palvelukeskeisen liiketoiminnan teoriaa, keskittyen arvonluonnin ja erityisesti arvon yhteisluonnin mekanismeihin. Teoreettisen viitekehyksen toinen pääteema esittelee asiakasdataa ja sen mahdollisuuksia B2B arvonluonnin kontekstissa. Tässä tutkimuksessa on käytetty konstruktiivista tutkimusotetta ja empiirinen tutkimusaineisto on kerätty pääasiassa kahdeksasta teemahaastattelusta. Teemahaastatteluissa haastateltavat ihmiset olivat sekä asiakasyrityksen työntekijöitä että yrityksen asiakkaita. Empiirisen tutkimuksen tavoitteina oli selvittää nykyisiä jälkimarkkinoiden ja palveluliiketoimintaan liittyviä asiakasmarkkinoinnin käytäntöjä, sekä niihin liittyviä haasteita. Haastatteluissa selvitettiin myös tulevaisuuden mahdollisuuksia asiakasdatan käyttöön markkinoinnissa sekä arvon yhteisluonnissa. Empiirinen aineisto kerättiin haastatteluin pääosin suomeksi ja käännettiin englanniksi. Tutkimus vahvistaa teoreettisen kirjallisuuden havainnot arvon yhteisluonnista, jossa arvon yhteisluonti B2B kontekstissa vaatii molempien osapuolten sitoutumista onnistuakseen. Tutkimuksessa havaittiin myös symmetrisen kommunikaation ja johdonmukaisen informaation tärkeys. Jälkimarkkinoiden myynnin kasvun vahvistaminen sekä arvon yhteisluonti edellyttää asiakasdatan tehokasta hyödyntämistä sekä koko organisaation symmetristä ja tehokasta sisäistä kommunikaatiota. Tutkimus tarjoaa systemaattisen näkökulman kuinka B2B palveluliiketoimintaa ja jälkimarkkinoiden tapoja voidaan kehittää kohti dataan perustuvaa yhteisarvonluontia. Tutkimus tarjoaa perustan jatkotutkimukselle, jossa tässä esitellyt konstruktiot voidaan implementoida ja kehittää edelleen. Lisäksi, jatkotutkimus voi tutkia ja kehittää reaaliajassa kerättyyn ja analysoituun asiakasdataan pohjautuvia yhteisarvonluonnin sovelluksia.
Keywords: customer data, value co-creation, marketing, service business, B2B after-sales